Peran Bank Syariah dalam Membangun Kemitraan untuk Pencapaian Tujuan Pembangunan Berkelanjutan (Sustainable Development Goals Poin 17) di Sumatera Barat - Suci Ramadhani; Sandra Dewi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The role of Islamic banks in building partnerships to support the achievement of Sustainable Development Goal 17 in West Sumatra. This point emphasizes the importance of collaboration between various parties to achieve inclusive, sustainable, and equitable development. As financial institutions based on Islamic principles, Islamic banks have a social responsibility to play an active role in community economic empowerment and strengthen cross-sector collaboration, particularly in the micro, small, and medium enterprise (MSME) sector. This research used a descriptive qualitative method with secondary data obtained from the financial reports of Islamic banks in West Sumatra from 2021 to 2023. The results indicate that Islamic banks play a role in building partnerships through various financing schemes such as murabahah, mudharabah, and musyarakah. Furthermore, Islamic banks also establish strategic partnerships with local governments, businesses, and local communities to strengthen financial literacy, expand financial inclusion, and promote economic equality within the community based on Islamic values. Despite their significant contribution, Islamic banks still face challenges such as low public understanding of Islamic financial products, limited technology and human resources, and suboptimal synergy between institutions. Therefore, regulatory strengthening, innovation in Islamic banking services, and support from all stakeholders are needed to ensure effective partnerships and maximize their contribution to achieving the SDGs in West Sumatra.